The Dante Club : a novel - Pearl, Matthew (Random House Trade Paperbacks, 2004)
In 1865 Boston, an elite group of American Dante scholars, including Oliver Wendell Holmes and Henry Wadsworth Longfellow, is called upon to solve a series of murders inspired by scenes in Dante's "Inferno."